Nas fronteiras dos impactos expansionistas do capital sobre a saúde dos povos indígenas no brasil: questões para a compreensão do suicídio - ADSUARA, Carmen Hannud Carballeda (Associação Brasileira da Rede UNIDA, 2023)
Suicide among indigenous peoples in Brazil occupies a prominent place in the concern of several leaderships, indigenists and intellectuals. However, often the look at this phenomenon becomes detached from the social fabric that permeates the relationship between indigenous and nonindigenous society. Thus, the present article proposes to look at the available literature on suicide, based on the central assumption that it is inseparable from the contradictory process of violence and embezzlement to which they have been subjected despite the guarantee of their rights under international agreements. Thus, considering the structurehistory movement of cultures, the text addresses suicide as a collective health problem for the population and indigenous peoples in an inseparable way from the history of genocide in the context of borders, so there is a epistemic transformation caused by the penetration of territories.